Intravenous immunoglobulin–related hemolysis in patients treated for Kawasaki disease. Issue 2 (14th July 2015) - Luban, Naomi L.C.; Wong, Edward C.C.; Henrich Lobo, Rodolfo; Pary, Philippe; Duke, Sarah
<x xml:space="preserve">Abstract</x> BACKGROUND Kawasaki disease (KD) is an idiopathic, multisystem disorder characterized by vasculitis of arteries, veins, and capillaries, affecting pediatric patients, and is the leading cause of acquired heart disease in childhood. The mainstays of therapy for KD are high‐dose intravenous immunoglobulin (IVIG) and aspirin, which are thought to prevent or modify the most serious cardiac sequelae. A well‐documented complication of high‐dose IVIG infusion in adults is hemolytic anemia due to passive transfer of anti‐A and anti‐B. Risk factors for hemolysis in another case series included patient blood group (group A, B, or AB), a high cumulative dose of IVIG, and concomitant inflammation documented by one or more markers like ferritin, fibrinogen, erythrocyte sedimentation rate, or C‐reactive protein. STUDY DESIGN AND METHODS A 3‐year retrospective case review of patients previously recognized with apparent IVIG‐related hemolytic anemia identified by standard blood bank testing was performed at a tertiary care pediatric hospital. RESULTS Five patients were identified with severe anemia each requiring RBC transfusion for anemia. All five patients demonstrated a positive direct antiglobulin testing. Four of five patients had anti‐A, anti‐B, and/or anti‐A1 with elution assays. All patients had signs of extravascular hemolysis with reticulocytosis, spherocytosis, and other hemolysis markers. One child died. CONCLUSION Our cases represent dose‐dependent hemolysis caused by IVIG in association with severe anemia requiring transfusion with an average yearly incidence rate of 0.36%. Hemolysis is an underrecognized complication of IVIG administration. KD patients are at greater risk for anemia because of their lower baseline hemoglobin concentration, underlying acute inflammation, and oxygen requirements during acute illness.